Issues and Developments in international Trade Policy : Occa Paper No.63. (Occasional Papers; Occasional Paper, 1988)
This paper discusses reviews major issues and developments in the trade area and outlines the problems in the multilateral trading system that governments face as they seek to liberalize trade in the Uruguay Round of trade negotiations. The paper's emphasis is on policy developments in the major trading nations as they relate to trade in both industrial and agricultural products. The survey also includes a review of trade policies in developing countries and refers to available quantitative evidence on protectionism wherever possible. The increased use of nontariff measures reflects, in part, the fact that most industrial countries have 'bound' a considerable proportion of their tariffs, particularly on industrial products, at relatively low levels. Restrictions are particularly widespread in industries suffering from excess capacity (such as steel) and where comparative advantage has generally shifted to developing countries. The lack of major liberalization in agriculture in the US-Canada Free Trade Agreement has led some industrial countries to suggest that the US interest in multilateral negotiations is now primarily in agriculture and in some selected new areas, such as telecommunications, banking, and patent protection.